2006
DOI: 10.1111/j.1468-3083.2006.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical and psychosocial outcome of patients with occupational contact dermatitis in Israel

Abstract: Considerable working time is lost because of unemployment or sick leave due to OCD. Only a small proportion of eligible patients with OCD apply for disability compensation and an even smaller proportion receive it. Our study demonstrates the significance of OCD to the psychosocial aspects of workers' lives and emphasizes that the assessment of OCD outcome should relate not only to the medical but also to the psychosocial aspect of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 32 publications
2
26
2
Order By: Relevance
“…One study reported a small effect of OCD on QoL [39], three found a moderate effect [29, 33, 36], and one reported a large effect on QoL [32]. The most affected domains in the DLQI were symptoms and feelings [29, 30, 33, 36, 39] and work [29, 32, 33, 35]. The large variation may relate to different methods of patient selection, such as from referral clinics and workplaces, and duration of followup.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study reported a small effect of OCD on QoL [39], three found a moderate effect [29, 33, 36], and one reported a large effect on QoL [32]. The most affected domains in the DLQI were symptoms and feelings [29, 30, 33, 36, 39] and work [29, 32, 33, 35]. The large variation may relate to different methods of patient selection, such as from referral clinics and workplaces, and duration of followup.…”
Section: Resultsmentioning
confidence: 99%
“…Seven were follow-up studies [29, 31, 32, 3436, 39], of which five were performed retrospectively [29, 31, 34, 35, 39], while four studies were cross-sectional [30, 33, 37, 38]. The study participants were either recruited from dermatology clinics [2933, 35, 39] or national registries [34, 3638] and the study samples ranged in size from 36 to 560 people. Although the participants in all studies had a clinical diagnosis made at first contact, in only 8 studies were further investigations done to confirm the clinical diagnosis [3032, 3437, 39].…”
Section: Characteristics Of Studies On Qol and Ocdmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] The outcome of studies on quality of life in patients suffering from contact dermatitis allows a better understanding of the magnitude, complexity and severity of the problem of contact dermatitis and points out the need for preventive measures and adapted assistance.…”
Section: Introductionmentioning
confidence: 99%